ASPARTATE PLATELET RATIO INDEX AS A PREDICTOR OF SEVERITY OF FIBROSIS IN CHRONIC HEPATITS C - NARAYANAN, KANNAN; ZACHARIAH, SUE ANN; KURIAN V, SHEELA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Hepatitis C is an important emerging cause for chronic liver disease in India, with high risk for chronicity and hepatocellular carcinoma. Chronic hepatitis C (CHC) is the most common cause for chronic liver disease and cirrhosis, and liver transplantation. Liver biopsy is the gold standard for evaluation of fibrosis - however it remains fraught with drawbacks and limitations. The aspartate aminotransferase-to-platelet ratio index (APRI), a tool with limited expense and widespread availability is a promising non-invasive alternative to liver biopsy for detecting hepatic fibrosis in CHC.(1) The objectives of the study were to determine the association between APRI and severity of fibrosis in Hepatitis C (2) and to describe the clinical profile of patients with Hepatitis C. Methods: A cross-sectional descriptive study in 60 patients diagnosed with hepatitis C for more than 6 months admitted to the General Medicine and Medical Gastroenterology Departments of Govt Medical College, Kottayam. Data were collected with a structured pro forma and analyzed using SPSS. Results: 35 of 60 patients belonged to METAVIR F3 (severe fibrosis) and F4 (cirrhosis). An APRI of 0.5 was associated with a finding of F3 or F4 with a sensitivity of 97.14% and a specificity of 88%. 31 of the 60 patients belonged to F4. An APRI of 1.5 or more was a predictor for cirrhosis with a sensitivity of 93.1% and specificity of 96.77%. The positive predictive value of cirrhosis APRI threshold >1.5 is 96.4%.